Optimizing DNA extraction protocols for the diet analysis of a baleen whale (Eubalaena australis) - Parikh, Aashi; O'Rorke, Richard; Carroll, Emma; Vermeulen, Els; Harcourt, Robert; Chariton, Anthony (Zenodo, 2024)
Faecal metabarcoding is widely used for mammalian diet analysis. However, most extraction protocols are designed to use high molecular weight genomic DNA, making short sequences of digested DNA challenging to extract. Here, we compared a phosphate buffer DNA extraction method along with two commercial extraction kits (the QIAamp Fast DNA Stool Mini Kit and the PowerSoil kit) with the following variations: 1) different durations of incubation in a phosphate buffer (1 hour and 24 hours), 2) processing of both pellet and supernatant from phosphate buffer incubation, and 3) two different concentrations of DNA binding buffer to examine prey DNA in southern right whale ( Eubalaena australis, SRW) faecal matter. We found that the choice of extraction protocol influenced richness, diversity, and composition of eukaryotes (18S rDNA) and crustaceans (Crust16S mtDNA) detected in SRW faecal samples. The PowerSoil protocol performed well for both markers, delivering the highest target richness for 18S rDNA and highest diversity for Crust16S mtDNA, while the pellet of the phosphate buffer yielded the highest richness for Crust16S mtDNA. The phosphate buffer supernatant protocols produced the lowest results for richness and diversity. Taxonomic composition in the supernatant alone was affected by the duration of incubation and the concentration of binding buffer and was also distinct from the corresponding pellet. Our results reinforce the importance of having clear targets prior to selecting a method for faecal metabarcoding, as the specific aims (e.g. identifying richness versus diversity) will inform the choice of extraction protocol. Southern right whale faecal samples were collected opportunistically over decades of research. Faecal samples underwent DNA extraction using three different methods (phosphate buffer extraction, PowerSoil kit and QIAamp FAST DNA Stool Mini Kit) with modifications in each leading to 12 unique protocols. The modifications included: incubating samples for 1 hr and 24 hrs in a phosphate buffer, ...